The Impact of Immigration on the Human Capital of Natives - Chiswick, Carmel U. (Journal of Labor Economics, 1989)
"Implications of the quantity (number) and quality (skill) of immigration on the destination economy are analyzed, including impacts on value added, wages, quasi rents, rates of return, and the skill distribution of the native labor force. Quantity-quality trade-offs are considered for both immigrant and native workers. Medium- and long-run labor-supply responses by natives to immigrant-induced changes in wage rates are shown to have second-order effects which subtantively affect the impacts of immigrants. The impact of immigration policy depends on the quality as well as quantity of immigrants, the time horizon, and the speed of factor market adjustment."